From Waste to Aerogel: Upcycling of Post-Consumer Aluminum Beer Cans into Alumina-Based Aerogels with Improved Electrochemical Storage Performance - Bernardes, Joseane Caroline; da Costa Guedes, Hemily; Mascarelli, Thales [UNESP]; da Silva, Vinicius Augusto [UNESP]; Marchiori, Leonardo [UNESP]; Fontana, Klaiani Bez; Chaves, Eduardo Sidinei; Rambo, Carlos Renato; Ribeiro, Sidney José Lima [UNESP]; Ferreira-Neto, Elias Paiva [UNESP] (American Chemical Society (ACS), 2025)
In this study, we report a facile, template-free, and sustainable upcycling route for the synthesis of alumina-based aerogels from post-consumer aluminum beer can waste. The developed route employs different parts of aluminum beer cans to yield phase-pure γ-AlOOH and γ-Al2O3 aerogels with high surface area, mesoporosity, a fine microstructure of interconnected nanoflakes/nanofibers, and good thermal stability, displaying properties that are comparable, or even superior to, those of control samples prepared from high-purity AlCl3. Notably, we demonstrate that incorporation of impurities from the can alloy composition, particularly Mn, influences the optical, structural, and electrochemical behavior of prepared alumina-based aerogels, leading to a significantly improved energy storage performance in comparison to aerogels prepared with high-purity precursors. These findings establish a circular-economy-based approach to upcycle aluminum packaging waste into advanced, nanostructured aerogel materials with promising applications in energy storage, catalysis, thermal insulation, adsorption, sensing, and optical devices.